Erratum: Magnetic droplet nucleation boundary in orthogonal spin-torque nano-oscillators - Chung, Sunjae; Eklund, Anders; Iacocca, Ezio; Mohseni, Seyed Majid; Sani, Sohrab R.; Bookman, Lake; Hoefer, Mark A.; Dumas, Randy K.; Åkerman, Johan (Nature communications, 2016)
Nature Communications 7 Article number: 11209 (2016); Published: 18 April 2016; Updated: 12 May 2016. The affiliation details for Mark A. Hoefer are incorrect in this Article. The correct affiliation details for this author are given below: Department of Applied Mathematics, University of Colorado, Boulder, Colorado 80309-0526, USA.